Peranan Rekrutmen Karyawan Dalam Menghasilkan SDM Berkualitas Pada UMKM Hana Ramen Karawang - Rizkyani Salsabila; Feby Ayu Nurfita; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this visit is to find out the Role of Employee Recruitment in producing Quality Human Resources at UMKM Hana Ramen Karawang. To support the results of this visit, the authors used a descriptive method through observation conducted by interviews and documentation. The employee recruitment process at Hana Ramen UMKM uses a social media recruitment system through the social media platforms Facebook, Instagram and WhatsApp and uses informal methods by word of mouth. The results show that recruiting quality human resources will have a positive impact on brand success, competitiveness, and the sustainability of a business. The role of Human Resources is very much needed in a company or UMKM so that it can be used as an asset in achieving success in achieving goals. The success of a company or MSMEs in maintaining the company's existence begins with efforts to manage human resources, especially in increasing work effectiveness and efficiency optimally. Human resources are the most important element in a company or MSME so that they can run well, without these elements or the poor quality of human resources, it will be difficult for the company to run and operate properly even though other resources have been fulfilled. Therefore, to produce quality human resources, good employee recruitment is needed.Â